Aphids harbouring different endosymbionts exhibit differences in cuticular hydrocarbon profiles that can be recognized by ant mutualists - Corinne Hertaeg (Nature Portfolio, 2021)
Abstract Cuticular hydrocarbons (CHCs) have important communicative functions for ants, which use CHC profiles to recognize mutualistic aphid partners. Aphid endosymbionts can influence the quality of their hosts as ant mutualists, via effects on honeydew composition, and might also affect CHC profiles, suggesting that ants could potentially use CHC cues to discriminate among aphid lines harbouring different endosymbionts. We explored how several strains of Hamiltonella defensa and Regiella insecticola influence the CHC profiles of host aphids (Aphis fabae) and the ability of aphid-tending ants (Lasius niger) to distinguish the profiles of aphids hosting different endosymbionts. We found significant compositional differences between the CHCs of aphids with different infections. Some endosymbionts changed the proportions of odd-chain linear alkanes, while others changed primarily methyl-branched compounds, which may be particularly important for communication. Behavioural assays, in which we trained ants to associate CHC profiles of endosymbiont infected or uninfected aphids with food rewards, revealed that ants readily learned to distinguish differences in aphid CHC profiles associated with variation in endosymbiont strains. While previous work has documented endosymbiont effects on aphid interactions with antagonists, the current findings support the hypothesis that endosymbionts also alter traits that influence communicative interactions with ant mutualists.